If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = 4(x + -1) Reorder the terms: 11 = 4(-1 + x) 11 = (-1 * 4 + x * 4) 11 = (-4 + 4x) Solving 11 = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 11 + -4x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 11 + -4x = -4 + 0 11 + -4x = -4 Add '-11' to each side of the equation. 11 + -11 + -4x = -4 + -11 Combine like terms: 11 + -11 = 0 0 + -4x = -4 + -11 -4x = -4 + -11 Combine like terms: -4 + -11 = -15 -4x = -15 Divide each side by '-4'. x = 3.75 Simplifying x = 3.75
| x^2-100x+3025=0 | | r/(-51)=-156 | | -w=39 | | 5x+27=4x+28 | | -22p-6(6-5p)=4(p-3)-36 | | 2ax+5=6x+1 | | X^29x+14=0 | | 3v-6=-12 | | -5w=22 | | 15+3x=39+x | | 5ax+5=6x+1 | | 15x-9=8x+21 | | -9x+3x=18 | | (4x+6)+90=136 | | 21-(x+6)=8x-3 | | 5x-4x+3x-16=8 | | 136+90+(4x+6)=360 | | -(6y+w)-2(-2w+4y)= | | w=39 | | 0.35/3=18/c | | 4x+10=6x+15 | | x-2(x+3)=0 | | (3z+5)(7-z)=0 | | 20=-8w+5(w-2) | | 15x+3=49 | | S/3-8=23 | | 0=-16t^2+184t+20 | | 6.6x-3+x-1.7=0 | | 5x+15=4x+12 | | -2p-4=10 | | 2b+(-9)=-17 | | 2a-24=3b |